Controlador de demanda e emulador do consumidor residencial para manutenção do conforto do usuário em Smart Grids - Maciel, Savio Alencar (2014)
This work presents an approach to control demand for residential low voltage consumers, aiming to improve energy efficiency in Smart Grids. Initially, an emulator of residential electric loads is modeled based on the literature. The emulator consists of a reservoir for water heating model, the model of an air conditioner and also models of consumption for lighting, televisions and a refrigerator. The implementation and simulation were performed using software Matlab. The demand control algorithms are investigated in order to verify its performance when applied to the set of residential loads. These algorithms typically perform control demand from a system of priorities. Still, from this analysis it demonstrates that these algorithms consider levels of user comfort, but do not allow the drive of two or more loads in the same period of residence if the demand exceeds the limit. Therefore, we propose a control algorithm that uses Rosenbrock search of demand adaptive method, aiming to overcome these limitations. The proposed procedure performs the operation of residential loads gradually considering priority levels and parameters of comfort of users. It is shown through simulations and experiments using the proposed method can perform the activation of several concurrently loads, provided they comply with the limits of comfort and demand. To obtain the experimental results demand the controller was implemented in an embedded system and tested with the emulator residential electrical loads implemented in a HIL (Hardware-in-theloop) architecture. Analyzing the results, it was observed that the power consumption is the same for all scenarios simulated and demand remained below parametric limits. But with the demand limiter active, we obtained a reduction of up to 52% in heat water using the demand controller adaptive, so the discomfort of the users can be minimized.